Collaborative Learning Strategies in Improving Students' Thinking Skills - Abdil latif; Intan Purnama; Nenden Hayati; Euis Latipah (Penerbit Hellow Pustaka, 2026)
Collaborative learning strategies have become a major focus in efforts to improve students' thinking comprehension at various levels of education. This approach involves students in interactive activities with peers that allow them to share ideas, discuss, and solve problems together. This study aims to measure the effectiveness of collaborative learning strategies in improving students' critical and creative thinking skills. Through qualitative methods, data were collected from classroom observations, interviews with students and teachers, and analysis of learning documents. The results showed that students involved in collaborative learning showed significant improvements in analytical thinking and problem-solving skills. In addition, collaborative learning also contributed to the development of students' social and communication skills, which are very important in the context of 21st century education. Reflections from this practice indicate that a collaborative learning environment creates a more dynamic and interactive atmosphere, so that students are more motivated to learn. Thus, collaborative learning strategies not only improve understanding of the material but also equip students with the thinking skills needed to face future challenges. This study supports the wider application of collaborative learning strategies in the education curriculum.